2018
DOI: 10.1007/s11356-018-2849-6
|View full text |Cite
|
Sign up to set email alerts
|

Study on the copper(II)-doped MIL-101(Cr) and its performance in VOCs adsorption

Abstract: The metal-organic framework (MOF) materials, MIL-101(Cr), and copper-doped MIL-101(Cr) (Cu@MIL-101(Cr)) were prepared through hydrothermal method and were used to remove volatile organic compounds (VOCs) in this study. Morphological characterization demonstrated that MIL-101(Cr) and Cu-3@MIL-101(Cr) were octahedral crystal, with specific surface area of 3367 and 2518 m/g, respectively. The results of XRD, TG, and FTIR showed that the copper doping procedure would not alter the skeleton structure, but it would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 47 publications
4
14
0
Order By: Relevance
“…Fourier transform infrared (FT-IR) spectrums of MIL-101(Cr) and M@MIL-101(Cr) were exhibited in Figure 2, which are similar to ones of MIL-101(Cr) reported before, [35,36] indicating that MIL-101(Cr) and M@MIL-101(Cr) were prepared swimmingly and the functional groups of MIL-101(Cr) were retained after the incorporation of M 2 + . The stretching and bending vibrations corresponding to 3431 and 1620 cm À 1 were caused by water, which was absorbed on the MIL-101(Cr), respectively.…”
Section: Catalyst Characterizationsupporting
confidence: 78%
“…Fourier transform infrared (FT-IR) spectrums of MIL-101(Cr) and M@MIL-101(Cr) were exhibited in Figure 2, which are similar to ones of MIL-101(Cr) reported before, [35,36] indicating that MIL-101(Cr) and M@MIL-101(Cr) were prepared swimmingly and the functional groups of MIL-101(Cr) were retained after the incorporation of M 2 + . The stretching and bending vibrations corresponding to 3431 and 1620 cm À 1 were caused by water, which was absorbed on the MIL-101(Cr), respectively.…”
Section: Catalyst Characterizationsupporting
confidence: 78%
“…Metal-organic frameworks (MOFs), as novel adsorbents, have been attracted considerable attention owing to their excellent specific surface and porosity, as well as tunable topologies (Sun et al, 2014; Ahmed and Jhung, 2016; Li et al, 2018; Lin et al, 2018). Importantly, MOFs have been developed as attractive candidates for VOCs adsorption (Duan et al, 2013; Vellingiri et al, 2016, 2017; Wang et al, 2018). Hu et al (2018) reported that UiO-66 had the high adsorption capacities of chlorobenzene (4.94 mmol/g) and acetaldehyde (9.42 mmol/g).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, some MOFs nanomaterials with large surface area and high thermal stability are hydrophobic and show great potential as efficient sorbents for VOCs. In the past few years, great efforts have been conducted to depict the excellent adsorption capacity of MOFs against VOCs [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%